Usage of peritoneal dialysis in infants following correction of congenital heart defects - O. Yakimishen; S. Boyko; T. Malysheva; S. Spisarenko; Y. Truba (Ukrainian Journal of Cardiovascular Surgery, 2019)
Children with congenital heart disease have an increased risk of acute kidney injury (AKI) after cardiac surgery. Conditions preceding this complication include: acute inflammatory reaction to artificial blood circulation and postoperative hemodynamic instability, ischemia or reperfusion injury, circulating mediators of inflammation and myoglobin, postoperative hemolysis, attachment of the infectious agent, congestive heart failure, and renal failure. One of the methods for resolving this condition is peritoneal dialysis (PD), especially relevant for newborns and infants.Objective. To analyze our experience of using peritoneal dialysis in children under 1 year with acute kidney injury after cardiac surgery and to identify the factors causing this complication.Materials and methods. The retrospective analysis of efficacy of peritoneal dialysis and risk factors for AKI in children under 1 year of age, following cardiac surgery in National M. M. Amosov Institute of Cardiovascular Surgery National of Ukraine period from 2014-2018 years was performed. During this period, 620 children underwent surgical interventions, the mean age was 6±5.4 months, the mean weight was 6±4.2 kg.Results. In the postoperative period, 112 (18%) patients developed acute kidney injury, and of those peritoneal dialysis was used in 57 (50.2%). The indications for PD initiation included oliguria (n=31), anuria (n=18), metabolic acidosis (n=8). The average time between cardiac surgery and AKI was 4±16.8 hours, and 12±6.5 hours between AKI and PD initiation. PD usage lasted 8±5.8 days. The following complications were reported: peritonitis in five patients, and PD catheter malfunction in 11 patients. Hospital mortality associated with PD was 42% (n=24). Patients with PD had a lower weight (p=0.004) and had longer artificial circulation (p=0.004), inotropic support (p=0.002), and mechanical ventilation (p=0.003). However, in regression analysis, only the time of artificial circulation (odds ratio: 1.021; 95% confidence interval: 0.998-1.027; p=0.032) remained predictive.Conclusion. Peritoneal dialysis is an effective osmotic ultrafiltration for the children under 1 year with acute kidney injury after cardiac surgery. Only the time of artificial circulation is predictive.